Adsorption Thermodynamic and Kinetic Studies of Methyl Orange onto Sugar Scum Powder as a Low-Cost Inorganic Adsorbent. (27th June 2020) - El maguana, Y.; Elhadiri, N.; Benchanaa, M.; Chikri, R.
Abstract : In the present study, batch adsorption experiments were carried out to investigate the removal of methyl orange (MO) from aqueous solution using sugar scum powder as an effective inorganic adsorbent which is a cheap precursor and abundant. The characteristics of this material were determined using XRD, SEM/EDX, and FTIR. The adsorption performance of sugar scum powder was evaluated using MO as the model adsorbate. Effects of various parameters such as initial dye concentration, contact time, and adsorbent dose were studied. The adsorption process can be best described by the pseudo-second-order kinetic and Langmuir adsorption isotherm models. Maximum monolayer adsorption capacity for MO removal was found to be 15.24 mg/g at temperature 22°C and pH 7.2. Moreover, thermodynamic parameters suggested that the adsorption of MO onto sugar scum powder was a spontaneous and exothermic process. The results demonstrated that sugar scum is a suitable precursor for the preparation of efficient adsorbent for dye removal from wastewater.